The Influence of Product Attributes Evaluation towards Proton Car Purchase Decision in China - Li, Yuan (2011)
Product attributes of a product influence customers’ purchase decision, it plays an indispensable role in customers’ purchase decision making process. This study is conducted to identify the product attributes that influence Chinese car buyers’ Proton car purchase decision, and discover the most influential product attribute that make Chinese people’s Proton car purchase decision, then find out the most dominating income group of people that purchase Proton cars in China market. Findings of this research propose several recommendations for both Proton company and Chinese local auto firms, the identification of product attribute such as performance delivery, quality satisfaction and other product attributes influencing on Chinese people’s Proton car purchase decision will be constructive for Proton’s marketing communication scheme and marketing mix strategy in China market, moreover, the identified the income groups of people that purchase Proton cars will assist marketers with more accurate market segment, market positioning as well as target market. The most important contribution of this research is the findings on what product attributes Chinese car buyers concentrate when they purchase foreign cars.